Genetic and expression analysis of cattle identifies candidate genes in pathways responding to Trypanosoma congolense infection - Noyes, H.A.; Brass, A.; Obara, Isaiah; Anderson, S.I.; Archibald, A.L.; Bradley, D.G.; Fisher, P.; Freeman, A.R.; Gibson, John P.; Gicheru, M.; Hall, L.; Hanotte, Olivier H.; et al. (National Academy of Sciences, 2011)
We review the global dynamics of livestock disease over the last two decades. Our imperfect ability to detect and report disease hinders assessment of trends, but we suggest that, although endemic diseases continue their historic decline in wealthy countries, poor countries experience static or deteriorating animal health and epidemic diseases show both regression and expansion. At a mesolevel, disease is changing in terms of space and host, which is illustrated by bluetongue, Lyme disease, and West Nile virus, and it is also emerging, as illustrated by highly pathogenic avian influenza and others. Major proximate drivers of change in disease dynamics include ecosystem change, ecosystem incursion, and movements of people and animals; underlying these are demographic change and an increasing demand for livestock products. We identify three trajectories of global disease dynamics: (i) the worried well in developed countries (demanding less risk while broadening the circle of moral concern), (ii) the intensifying and market-orientated systems of many developing countries, where highly complex disease patterns create hot spots for disease shifts, and (iii) the neglected cold spots in poor countries, where rapid change in disease dynamics is less likely but smallholders and pastoralists continue to struggle with largely preventable and curable livestock diseases.